Association between sexual function in women and sleep quality - Martínez Vázquez, Sergio; Hernández Martínez, Antonio; Peinado Molina, Rocío Adriana; Martínez Galiano, Juan Miguel (Frontiers in Medicine, 2023)
Objective: To determine the relationship between sexual dysfunction and sleep disorders.Methods: Observational study was conducted in 2021 and 2022 including 975 Spanish women over 18 years of age. The Women's Sexual Function Questionnaire (WSF) was used as a source of information, and the Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality.A bivariate and multivariate analysis was performed using binary logistic regression, adjusting for confounding variables. Crude (OR) and adjusted (aOR) odds ratios were estimated with their respective 95% confidence intervals (CI).Results: Around 29.2% (285) of the women presented some type of sexual dysfunction, and 73.4% (716) showed sleep disturbance with scores  5 on the PSQI scale. The mean score on the PSQI was 8.23 points (SD=3.93). All the dimensions of the sexual function scale were statistically related to sleep disturbance (p<0.05), except for sexual activity and the reasons for sexual activity not having penetration. In the multivariable analysis, women with sexual dysfunction presented an aOR of sleep disturbance of 1.88 (95% CI:1.29-2.76) compared to women without dysfunction.Global sexual dysfunction and almost all the dimensions that make up sexual function are related to changes in sleep quality.